On the Viability of Conditional Assistance Programs - Mayer, Wolfgang (IMF Working Papers; Working Paper ;, 2005)
Economic adjustment and reform programs, including those supported by international financial institutions (IFIs), must cope with informational asymmetries and special interest politics. This presents a particularly serious issue when IFIs make structural economic reforms a condition for providing economic assistance. This paper examines what conditions must be satisfied to make conditional assistance programs viable; that is, to ensure that the assistancereceiving government not only takes the assistance but also implements reforms, without compromising the country's political stability and the IFI's financial integrity. It is pointed out that tightly budgeted conditional assistance programs never bring about reforms, that the IFI's cost of viable programs rises with the dependence of the government on domestic interest groups, and that unconditional assistance might be viable when conditional assistance is not.